A Base Nacional Comum Curricular (BNCC) e a formação inicial de professores: análise do Curso de Pedagogia do CCHSA/UFPB a partir do ciclo de políticas de Stephen Ball - Rodrigues, Adriege Matias (2020)
The objective of the dissertation was to analyze the effects on the initial training of teachers of the Pedagogy Course at CCHSA / UFPB from the new directions of the Common Curricular National Base for Basic Education. It is understood that curricular changes in basic education directly imply formative changes in initial training courses, so the focus of study is the Pedagogy Course at CCHSA / UFPB. The research approach was qualitative, anchored in Ball's „policy cycle‟, consisting of five contexts: Context of Influence, Context of Text Production, Context of Practice, Context of Results and Context of Political Strategy. The research subjects were students and teachers of the investigated course. To collect the data, the semi-structured interview was used as a research instrument. The analysis technique of the research findings was the content analysis. The categories arising from the research were the Initial Teacher Training and the BNCC. The analysis started from the theoretical-methodological approach of Stephen Ball and collaborators (BOWE; BALL & GOLD, 1992), which analyzes educational policy in a set of methods subjected to post-structural logic. To discuss the research findings, the theoretical contributions of Aguiar (2006, 2017, 2018), Pereira (2012, 2016), Akkari (2011), Ball (1987, 1992) and others were adopted. We emphasize that this reflection starts from the influences that this document received for its elaboration, both by researchers and professors, as well as politicians, bankers, among others. Thus, it was necessary to discuss the theoretical conception of the curriculum that underlies the propositions of this policy and how its directions can change the context of practice in the initial training of teachers. Current educational policy discussions do not occur as significantly and frequently as they should, which puts into question the continuing formation of the teacher teacher. For this reason, the research intended to contribute to the continuous debate on the compromises of the initial training of teachers of Pedagogy, with the approval of the BNCC, a national curriculum policy for basic education.